Hotspots of diversity in a clonal world: the Mediterranean moss Pleurochaete squarrosa in Central Europe - Grundmann, Michael; Koch, Marcus (Molecular ecology, 2008)
Diversity patterns of the dioecious haploid Mediterranean moss Pleurochaete squarrosa were analysed from Central and Northwest Europe using nuclear and chloroplast DNA sequencing and enzyme electrophoresis. Across 69 populations, 38 distinct haploid multilocus genotypes (MLGs) were detected, but nearly all populations were clonal. Only five MLGs occurred in more than two regions, and two diversity hotspots were detected. The Kaiserstuhl mountains in Southwest Germany harboured 34 MLGs, 25 being endemic within Central Europe. Levels of linkage disequilibrium and population structure in Kaiserstuhl populations were similar to levels and structure in sexually reproducing populations in the Mediterranean Basin. In the Moselle-Nahe area, some 250 km north, a comparably high allelic diversity, but no evidence of recombination, was detected. Genetic diversity measures were significantly lower than estimates obtained in the Mediterranean Basin and a GST of 0.89 signified extreme population differentiation. Mantel tests identified a positive correlation on genetic and geographical distance for distances up to 50 km. Seven nrITS and three cpDNA haplotypes were detected, their geographical structure mirroring enzyme data set results. Comparative analysis with Mediterranean data demonstrated multiple recolonization of Central Europe from both the Iberian Peninsula and the Balkans. A suture zone of genotypes was detected along the border of Belgium/France and Germany. Despite P. squarrosa having haploid spore and/or vegetative propagules dispersal, we found patterns of postglacial recolonization of Central Europe comparable with those reported in flowering plants and animals. This study demonstrates the importance of comparative research on population genetics and phylogeography of a diverse range of organisms.